Review of orthopaedics - Miller, Mark D. (Elsevier/Saunders, 2012)
A review of key orthopaedic knowledge that helps you for exam preparation at various levels of orthopaedic training and incorporates the advanced in scientific and clinical knowledge, as well as the emphases on key examinations